2010
DOI: 10.1111/j.1747-0765.2010.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Succession and community composition of ammonia-oxidizing archaea and bacteria in bulk soil of a Japanese paddy field

Abstract: The present study describes succession in the abundances of ammonia‐oxidizing archaea (AOA) and ammonia‐oxidizing bacteria (AOB) in the upland and flooded bulk soils of a Japanese rice paddy field over 2 years using a quantitative polymerase chain reaction of both crenarchaeotal and betaproteobacterial ammonia monooxygenase alpha subunit (amoA) genes. A marked increase in the abundance of AOA amoA gene was observed in upland bulk soil after plowing, drainage and rice harvesting. A marked increase was also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 43 publications
(102 reference statements)
3
16
0
Order By: Relevance
“…The amoA sequences of the strain in AOA-DW were 98.2 to 98.5% identical to those of clones from the sediment of Lakes Acton, Delaware, and Pleasant Hill (C. Li and A. Bollmann, unpublished), 98.5% identical to those of clones from the freshwater sediment in the San Francisco Bay (38), and 98.1% identical to those of clones from a drinking water distribution system in The Netherlands (59). The amoA sequences of the strain in AOA-AC5 were 99% identical to the amoA sequence of a clone from a paddy soil in Japan (18). The strain in the third enrichment culture, AOA-AC2, is closely related to "Ca.…”
Section: Resultsmentioning
confidence: 76%
“…The amoA sequences of the strain in AOA-DW were 98.2 to 98.5% identical to those of clones from the sediment of Lakes Acton, Delaware, and Pleasant Hill (C. Li and A. Bollmann, unpublished), 98.5% identical to those of clones from the freshwater sediment in the San Francisco Bay (38), and 98.1% identical to those of clones from a drinking water distribution system in The Netherlands (59). The amoA sequences of the strain in AOA-AC5 were 99% identical to the amoA sequence of a clone from a paddy soil in Japan (18). The strain in the third enrichment culture, AOA-AC2, is closely related to "Ca.…”
Section: Resultsmentioning
confidence: 76%
“…Paddy soil represents a special habirat wherein NH^-oxidizing communities are simultaneously shaped by flooding and fertilization. A recent study indicated that the abundance of AOA and AOB varies gready during the rice cultivation period (Fujii et al, 2010); however, the differential response of AOA and AOB community structures to long-term fertilization in paddy soils has not been fully addressed under in situ conditions. A long-term field fertilization experiment can serve as a model system to understand how anthropogenic disturbance may lead to changes in the soil NH^""" concentration, which in turn affects the AOA and AOB community structures under in situ conditions.…”
Section: Agriculturementioning
confidence: 99%
“…For a long time, it was believed that only AOB possess the amoA gene for ammonia monooxygenase, the key enzyme of ammonia oxidation (Rotthauwe et al 1997). The occurrence of AOB has been investigated in the flooding paddy soils, including surface soil, rhizosphere, and bulk soil, based on the amoA gene (Briones et al 2002;Nicolaisen et al 2004;Bowatte et al 2006Bowatte et al , 2007Chen et al 2008;Wang et al 2009;Chu et al 2010;Fujii et al 2010). Many studies indicate that Nitrosospira are predominant in the paddy soils (Bowatte et al 2006;Chen et al 2008;Chu et al 2010) while Nitrosomonas are prevalent in high-N fertilizer paddy soils or in the surface of rice roots (Briones et al 2002;Nicolaisen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The AOA are widespread in marine and terrestrial environments with high abundance values (Francis et al 2005;Leininger et al 2006;Wuchter et al 2006;He et al 2007;Shen et al 2008;Schauss et al 2009). Several studies also indicated that AOA outnumbered AOB in paddy soils (Chen et al 2008;Wang et al 2009;Fujii et al 2010), but the contribution of AOA to nitrification in the paddy soil is still unclear. Recently, some researchers found that archaea were not important for nitrification in their tested soils (Di et al 2009;Jia and Conrad 2009).…”
Section: Introductionmentioning
confidence: 99%